Cross-Cultural Impacts on Ethical Marketing Practices and Consumer Trust: Evidence from Hospitality Small and Medium-Sized Enterprises in Bali, Indonesia - Nurfadhilah, Nurfadhilah; Tijjang, Bakhtiar; Binti Abd Hafiz, Khalilah; Ikhrami, Siti Mirna (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
This study aims to analyze the influence of cross-cultural factors on ethical marketing practices and consumer trust, with Balinese cultural values serving as a moderating variable in the hospitality sector of MSMEs in Bali. A quantitative approach with an explanatory design was used through a survey of 200 respondents, and the data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0. The results show that four dimensions of Hofstede's culture have a significant effect on ethical marketing practices, namely Individualism vs. Collectivism (β = 0.221; p < 0.001), Power Distance (β = 0.103; p < 0.05), Uncertainty Avoidance (β = 0.189; p < 0.01), and Long-Term Orientation (β = 0.267; p < 0.001), while Masculinity vs. Femininity was not significant (p > 0.05). Ethical marketing practices have a strong influence on consumer trust (β = 0.612; p < 0.001), and Balinese cultural values (Tri Hita Karana) strengthen this relationship (β = 0.167; p < 0.01). These findings emphasize the importance of synergy between universal ethical values and local wisdom in building trust and sustainability in culture-based tourism businesses